Progress in Commutative Algebra 2 Closures, Finiteness and Factorization - Klingler , Lee; Francisco, Christopher; Sather-Wagstaff, Sean M.; Vassilev, Janet C. (De Gruyter, 2012)
This is the second of two volumes of a state-of-the-art survey article collection which originates from three commutative algebra sessions at the 2009 Fall Southeastern American Mathematical Society Meeting at Florida Atlantic University. The articles reach into diverse areas of commutative algebra and build a bridge between Noetherian and non-Noetherian commutative algebra. These volumes present current trends in two of the most active areas of commutative algebra: non-noetherian rings (factorization, ideal theory, integrality), and noetherian rings (the local theory, graded situation, and interactions with combinatorics and geometry). This volume contains surveys on aspects of closure operations, finiteness conditions and factorization. Closure operations on ideals and modules are a bridge between noetherian and nonnoetherian commutative algebra. It contains a nice guide to closure operations by Epstein, but also contains an article on test ideals by Schwede and Tucker and more.
Description based on print version record.
KU Select 2018: STEM Backlist Books
Keywords: Mathematics; Mathematics; Electronic books